The many faces of Iranian modernity - Ames, Robert Landau. (Piscataway)
xii, 201 sayfa
Keywords: “This study into both reformism and mysticism demonstrates both that mystical rhetoric appeared regularly in supposedly anti-mystical modernist writing and that nineteenth- and twentieth-century Sufis actually addressed questions of intellectual and political reform in their writing, despite the common assertion that they were irrationally traditional and politically quietist“ --